High-strength high-thermal-conductivity copper-based composite material and preparation method thereof

Through the process flow of ball mill mixing, drying, cold press forming and vacuum hot press sintering, copper-based composite materials are prepared, which solves the problems of difficult control of reaction conditions, uneven grains, and poor mechanical properties in the preparation method of copper-based composite materials in the prior art, and achieves copper-based composite materials with high strength, high thermal conductivity and excellent mechanical properties.

CN119876683APending Publication Date: 2025-04-25THREE GORGES INTELLIGENT ENG CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411840504.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the existing preparation methods of copper-based composite materials, reaction conditions are difficult to control, grains are uneven, and mechanical properties are poor.

Method used

Using ball mill mixing, drying, cold press forming and vacuum hot press sintering, TiC and ZrC are added to the copper matrix, and the copper-based composite material is prepared by powder metallurgy method, and the sintering time, pressure, temperature and atmosphere are controlled to control grain growth.

Benefits of technology

The density of copper-based composite materials is significantly improved, so that the components are evenly distributed in the matrix, have stable structure, excellent performance, significantly improved mechanical properties, and significantly improved thermal conductivity and electrical conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005187863330000051
    Figure BDA0005187863330000051
Patent Text Reader

Abstract

According to the high-strength and high-thermal-conductivity copper-based composite material and the preparation method thereof, the technological process of ball-milling mixing, drying, cold press forming and vacuum hot pressing sintering is adopted, TiC and ZrC are added into a copper matrix to obtain the copper-based composite material, the copper-based composite material prepared through a powder metallurgy method has high controllability, and the high-strength and high-thermal-conductivity copper-based composite material can be obtained by controlling the sintering time. Growth of crystal grains is controlled according to sintering temperature, sintering pressure, sintering temperature, atmosphere and the like, so that the copper-based composite material with excellent performance is obtained. The compactness of the copper-based composite material can be remarkably improved, all components are evenly distributed in a matrix, the structure is stable, the obtained copper-based composite material is stable in performance, high in heat conductivity and excellent in electric conductivity, and the mechanical performance of the copper-based composite material is remarkably improved; the preparation process is free of pollution, the prepared copper-based composite material is high in purity, and the performance controllability of the copper-based composite material is high; the high-strength and high-thermal-conductivity copper-based composite material can be widely applied to the fields of electrician, aerospace and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials and relates to a copper-based composite material and a preparation method thereof. Background Art

[0002] Copper has been widely used in electrical and electronic, aerospace and other fields in recent years because of its good electrical conductivity, thermal conductivity and corrosion resistance. However, with the development of modern science and technology, many applications require materials to have not only good electrical conductivity and thermal conductivity, but also excellent wear resistance and various mechanical properties. However, the mechanical properties and wear resistance of pure copper itself are relatively low, which has limitations in many applications. Copper-based composite materials are composite materials with copper as the matrix and other materials as the reinforcement phase. Through the action of different materials, copper-based composite materials can maintain the good thermal conductivity and electrical conductivity of copper materials themselves, and have excellent mechanical properties that they do not have. However, in the current preparation method of copper-based composite materials, the reaction conditions are difficult to control, the grown grains are uneven, and the mechanical properties are poor. Summary of the invention

[0003] In order to solve the problems in the preparation method of the copper-based composite material described in the background technology that the reaction conditions are difficult to control, the grown grains are uneven, and the mechanical properties are poor, the present invention provides a high-strength and high-thermal conductivity copper-based composite material and a preparation method thereof.

[0004] The high-strength and high-thermal-conductivity copper-based composite material of the invention comprises the following components in percentage by mass: 1-3% TiC, 2-5% ZrC and the balance Cu.

[0005] The method for preparing the high-strength and high-thermal-conductivity copper-based composite material of the present invention comprises:

[0006] Step 1, ball milling Cu powder, TiC powder and ZrC powder to obtain composite powder;

[0007] Step 2, drying the composite powder;

[0008] Step 3: Take the dried composite powder and use a mold to cold press to obtain a green body;

[0009] Step 4: placing the green body into a vacuum sintering furnace for sintering to obtain a copper-based composite material.

[0010] Furthermore, in the step 1, the purity of the Cu powder is 99%, and the average particle size is less than 50 μm, the purity of the TiC powder is 98%, and the average particle size is less than 2 μm, and the purity of the ZrC powder is 98%, and the average particle size is less than 7 μm.

[0011] Furthermore, in the step 1, the Cu powder, TiC powder and ZrC powder are placed in a stainless steel vacuum ball mill, and ZrO 2 The mixture was then ball milled in a planetary ball mill to obtain composite powder.

[0012] Furthermore, in the step 1, the mass ratio of the ball mill to the ball-milled raw material is 10:1, the rotation speed of the planetary ball mill is 500 RPM, and the ball-milling time is 12-24 hours.

[0013] Furthermore, in step 1, ZrO 2 The diameter of the ball mill is 10-15mm.

[0014] Furthermore, in the step 2, the composite powder is placed in a vacuum oven for warm extraction, vacuum treated for 15 minutes and then dried, the vacuum oven temperature is set to 80° C., and the drying time is 10-12 hours.

[0015] Furthermore, in the step three, the mass of the dried composite powder weighed in each mold cold pressing molding is 1.8-2.0 g, the molding pressure is 100 MPa, and the holding time is 1 min.

[0016] Furthermore, in the step 4, the vacuum hot pressing sintering temperature is 800-1000° C., the sintering holding time is 10-20 min, and the pressure is 15-30 MPa.

[0017] Furthermore, in step 4, the temperature in the vacuum sintering furnace is measured by a thermocouple. Thermocouples are resistant to high temperatures and can make the temperature measurement in the furnace more accurate.

[0018] Compared with the prior art, the present invention adopts the process flow of ball milling, drying, cold pressing, and vacuum hot pressing sintering, and TiC and ZrC are added to the copper matrix to obtain a copper-based composite material. The copper-based composite material prepared by powder metallurgy has strong controllability, and the growth of grains can be controlled by controlling the sintering time, sintering pressure, sintering temperature and atmosphere, thereby obtaining a copper-based composite material with excellent performance. The present invention can significantly improve the compactness of the copper-based composite material, make each component evenly distributed in the matrix, and have a stable structure. The obtained copper-based composite material has stable performance, high thermal conductivity, and excellent electrical conductivity, and the mechanical properties of the copper-based composite material are significantly improved; and the preparation process is pollution-free, the prepared copper-based composite material has high purity, and the performance of the copper-based composite material is highly controllable; the high-strength and high-thermal-conductivity copper-based composite material of the present invention can be widely used in electrical engineering, aerospace and other fields. DETAILED DESCRIPTION

[0019] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0020] A high-strength and high-thermal-conductivity copper-based composite material consists of the following components in percentage by mass: 1-3% TiC, 2-5% ZrC and the balance Cu.

[0021] A method for preparing a high-strength and high-thermal-conductivity copper-based composite material, the specific steps are as follows:

[0022] Step 1: ball-milling Cu powder, TiC powder and ZrC powder to obtain composite powder.

[0023] Specifically, the purity of the Cu powder is 99% and the average particle size is less than 50 μm, the purity of the TiC powder is 98% and the average particle size is less than 2 μm, and the purity of the ZrC powder is 98% and the average particle size is less than 7 μm.

[0024] More specifically, Cu powder, TiC powder and ZrC powder were placed in a stainless steel vacuum ball mill, and ZrO 2 The ball mill is then used to mill the raw materials to obtain composite powder. The mass ratio of the ball mill to the raw materials is 10:1, the rotation speed of the planetary ball mill is 500RPM, and the milling time is 12-24h. 2 The diameter of the ball mill is 10-15mm.

[0025] Step 2: Drying the composite powder.

[0026] Specifically, the composite powder is placed in a vacuum oven for warm extraction, vacuum treated for 15 minutes and then dried, the vacuum oven temperature is set to 80° C., and the drying time is 10-12 hours.

[0027] Step 3: Take the dried composite powder and use a mold to cold-press it to obtain a green body.

[0028] Specifically, the mass of the dried composite powder weighed in each mold cold pressing molding is 1.8-2.0 g, the molding pressure is 100 MPa, and the holding time is 1 min.

[0029] Step 4: placing the green body into a vacuum sintering furnace for sintering to obtain a copper-based composite material.

[0030] Specifically, the temperature in the vacuum sintering furnace is measured by a thermocouple, the vacuum hot pressing sintering temperature is 800-1000° C., the sintering holding time is 10-20 min, and the pressure is 15-30 MPa.

[0031] Example 1

[0032] Weigh 29.1g Cu powder, 0.3g TiC powder and 0.6g ZrC powder into a stainless steel vacuum ball mill, and add 300g ZrO with a diameter of 10mm. 2 The ball mill was placed in a planetary ball mill for ball milling at a speed of 500 RPM for 12 h to obtain a composite powder.

[0033] The composite powder was placed in a vacuum oven for drying. After the powder was placed in the oven, the vacuum oven was evacuated for 15 minutes. The insulation temperature of the vacuum oven was set to 80°C and the insulation time was set to 10 hours.

[0034] Weigh 1.8 g of the dried powder and use a mold to cold press the powder. The molding pressure is 100 MPa and the holding time is 1 min. Repeat the above steps to prepare several green bodies.

[0035] The green body obtained by cold pressing is placed in a vacuum sintering furnace for sintering, and the heating rate is set to 2°C / min, the maximum temperature is 850°C, the holding time is 10min, and the pressure is 15MPa.

[0036] After testing, the Vickers hardness of the sintered copper-based composite material is 145.2H V , the tensile strength is 301MPa, the thermal conductivity and electrical conductivity are 344W / m·K and 89.5%IACS respectively.

[0037] Example 2

[0038] Weigh 27.6g Cu powder, 0.9g TiC powder and 1.5g ZrC powder into a stainless steel vacuum ball mill, and add 300g ZrO with a diameter of 10mm. 2 The ball mill was placed in a planetary ball mill for ball milling at a speed of 500 RPM for 24 h to obtain a composite powder.

[0039] The composite powder was placed in a vacuum oven for drying. After the powder was placed in the oven, the vacuum oven was evacuated for 15 minutes. The insulation temperature of the vacuum oven was set to 80°C and the insulation time was set to 12 hours.

[0040] Weigh 2.0 g of the dried powder and use a mold to cold press the powder. The molding pressure is 100 MPa and the holding time is 1 min. Repeat the above steps to prepare several green bodies.

[0041] The green body obtained by cold pressing is placed in a vacuum sintering furnace for sintering, and the heating rate is set to 2°C / min, the maximum temperature is set to 950°C, the holding time is set to 15min, and the pressure is set to 25MPa.

[0042] After testing, the Vickers hardness of the sintered copper-based composite material is 180.8HV , the tensile strength is 365MPa, the thermal conductivity and electrical conductivity are 286W / m·K and 74.4%IACS respectively.

[0043] Example 3

[0044] Weigh 28.2g Cu powder, 0.6g TiC powder and 1.2g ZrC powder into a stainless steel vacuum ball mill, and add 300g ZrO with a diameter of 10mm. 2 The ball mill was placed in a planetary ball mill for ball milling at a speed of 500 RPM for 12 h to obtain a composite powder.

[0045] The composite powder was placed in a vacuum oven for drying. After the powder was placed in the oven, the vacuum oven was evacuated for 15 minutes. The insulation temperature of the vacuum oven was set to 80°C and the insulation time was set to 10 hours.

[0046] Weigh 1.8 g of the dried powder and use a mold to cold press the powder. The molding pressure is 100 MPa and the holding time is 1 min. Repeat the above steps to prepare several green bodies.

[0047] The green body obtained by the cold pressing molding is placed in a vacuum sintering furnace for sintering, and the heating rate is set to 2°C / min, the maximum temperature is set to 900°C, the holding time is set to 10min, and the pressure is set to 20MPa.

[0048] After testing, the Vickers hardness of the sintered copper-based composite material is 171.6H V , the tensile strength is 354MPa, the thermal conductivity and electrical conductivity are 313W / m·K and 84.3%IACS respectively.

[0049] From Examples 1 to 3, it can be seen that the use of TiC and ZrC to prepare copper-based composite materials can significantly improve the strength and hardness of the material, reaching 145.2H V -180.8H V and 301Mpa-365MPa, the thermal conductivity and electrical conductivity are also significantly competitive among similar materials, which are 286W / m·K-344W / m·K and 74.4%IACS-89.5%IACS respectively.

[0050] The copper-based composite material prepared by the present invention was subjected to multiple performance tests, and the performance of HL105 copper material and H62 copper material was consulted and tested, and the obtained performance column is shown in Table 1.

[0051] Table 1 Performance column table

[0052]

[0053] It can be seen from Table 1 that the thermal conductivity and electrical conductivity of the copper-based composite material prepared by the present invention are much higher than those of HL105 copper and H62 copper; the tensile strength of the copper-based composite material prepared by the present invention is slightly lower than that of HL105 copper and H62 copper, but not significantly lower than that of HL105 copper and H62 copper; the Vickers hardness of the copper-based composite material prepared by the present invention is higher than that of HL105 copper, the Vickers hardness of the copper-based composite material prepared by the present invention is equivalent to that of H62 copper, and the minimum value of the Vickers hardness of the copper-based composite material prepared by the present invention is much greater than the maximum value of H62 copper. In short, the copper-based composite material prepared by the present invention has high thermal conductivity, excellent electrical conductivity, and good mechanical properties.

[0054] The embodiments described above are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application, and should all be included in the protection scope of the present application.

Claims

1. A high-strength and high-thermal-conductivity copper-based composite material, characterized in that: The invention comprises the following components in percentage by mass: 1-3% TiC, 2-5% ZrC and the balance Cu.

2. The method for preparing a high-strength and high-thermal-conductivity copper-based composite material according to claim 1, characterized in that: include: Step 1, ball milling Cu powder, TiC powder and ZrC powder to obtain composite powder; Step 2, drying the composite powder; Step 3: Take the dried composite powder and use a mold to cold press to obtain a green body; Step 4: placing the green body into a vacuum sintering furnace for sintering to obtain a copper-based composite material.

3. The method for preparing a high-strength and high-thermal-conductivity copper-based composite material according to claim 2, characterized in that: In the step 1, the purity of the Cu powder is 99%, and the average particle size is less than 50 μm, the purity of the TiC powder is 98%, and the average particle size is less than 2 μm, and the purity of the ZrC powder is 98%, and the average particle size is less than 7 μm.

4. The method for preparing a high-strength and high-thermal-conductivity copper-based composite material according to claim 3, characterized in that: In the step 1, Cu powder, TiC powder and ZrC powder are placed in a stainless steel vacuum ball mill, a ZrO2 ball mill is added, and then ball milling is performed in a planetary ball mill to obtain a composite powder.

5. The method for preparing a high-strength and high-thermal-conductivity copper-based composite material according to claim 4, characterized in that: In the step 1, the mass ratio of the ball mill to the ball-milled raw material is 10:1, the rotation speed of the planetary ball mill is 500 RPM, and the ball-milling time is 12-24 hours.

6. The method for preparing a high-strength and high-thermal-conductivity copper-based composite material according to claim 5, characterized in that: In the step 1, the diameter of the ZrO2 ball mill is 10-15 mm.

7. The method for preparing a high-strength and high-thermal-conductivity copper-based composite material according to claim 2, characterized in that: In the step 2, the composite powder is placed in a vacuum oven for warm extraction, vacuum treated for 15 minutes and then dried, the vacuum oven temperature is set to 80° C., and the drying time is 10-12 hours.

8. The method for preparing a high-strength and high-thermal-conductivity copper-based composite material according to claim 2, characterized in that: In the step 3, the mass of the dried composite powder weighed in each mold cold pressing molding is 1.8-2.0 g, the molding pressure is 100 MPa, and the holding time is 1 min.

9. The method for preparing a high-strength and high-thermal-conductivity copper-based composite material according to claim 2, characterized in that: In the step 4, the vacuum hot pressing sintering temperature is 800-1000° C., the sintering holding time is 10-20 min, and the pressure is 15-30 MPa.

10. The method for preparing a high-strength and high-thermal-conductivity copper-based composite material according to claim 9, characterized in that: In the step 4, the temperature in the vacuum sintering furnace is measured by a thermocouple.

Citation Information

Cited By

  • High-strength and high-conductivity C19400 copper-based composite material and preparation method thereof

    CN121976086A